Extensive purification of histone acetylase A, the major histone N-acetyl transferase activity detected in mammalian cell nuclei. - Esther J. Belikoff; L. Wong; Bruce Alberts (1980)
A concentrated, DNA-free extract of histone acetylase A was prepared from calf thymus tissues in two simple steps, which exploit the ability of polyethylene glycol to precipitate both nucleic acids and proteins from solutions containing high concentrations of salt (Alberts, B., and Herrick, G. (1971) Methods Enzymol. 21, 198-217). This extract was then chromatographed on four successive columns. The use of 75 microgram/ml of insulin as a carrier protein in all of these later steps, plus the inclusion of 1 M urea in some column buffers, has been useful in improving both the yield and reproducibility of the purification. The highly active enzyme obtained has a molecular weight of about 70,000, and the best fractions could be about 30% pure. Our data indicate that the acetylase A is only a very minor protein in cells, being present in perhaps a few thousand molecules per cell.